Integration of Environmental Social Issues in Sociology Learning to Build Social Awareness in High School Students - La Lulu Odebora; Roni Irawan (Yayasan Insan Mulia Bima, 2026)
This study aims to describe the integration of social and environmental issues in Sociology learning and analyze its role in shaping social awareness of grade X students of SMA Negeri 4 Ternate City. The study used a qualitative approach with a case study design. The research informants consisted of Sociology subject teachers and grade X students who were selected purposively. Data were collected through observation, interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña which includes data condensation, data presentation, and conclusion drawing. Data validity was obtained through source triangulation and technical triangulation. The results showed that the integration of social and environmental issues was carried out by linking learning materials with social phenomena close to students' lives, such as waste management, bullying, mutual cooperation, and environmental awareness through discussion activities, case analysis, presentations, and reflection. This approach makes learning more contextual, increases student participation, and facilitates understanding of Sociology concepts. In addition, the integration of social and environmental issues contributes to the formation of students' social awareness as demonstrated through the development of empathy, social responsibility, cooperation, environmental awareness, and participation in various social activities at school